THE INFLUENCE OF RECORDS MANAGEMENT ON EMPLOYEE WORK EFFICIENCY AT THE YOUTH, SPORTS, AND TOURISM DEPARTMENT (DISPORAPAR) OF TABALONG REGENCY - Norhidayah Norhidayah; Sri Agusmila Aneta Herlinda; Najimatul Munawarah (PPPM STIA Amuntai, 2026)
This study investigates the impact of suboptimal Records Management, characterized by irregular classification systems and a lack of document disposal, on employee performance at the Department of Youth, Sports, and Tourism of Tabalong Regency. Using a quantitative associative approach with a census method (total sampling) involving 32 respondents, the data were analyzed using SPSS 25 through questionnaires. The results of the simple linear regression and t-tests confirm a positive and significant influence, evidenced by a calculated t-value exceeding the critical t-table value and a correlation coefficient of 0.828, indicating a very strong relationship. The findings reveal that Records Management contributes 68.5% to the variability of work efficiency, where every improvement in the archival system increases efficiency by 1.251 points. Consequently, it is recommended that the agency evaluate governance, enforce discipline, and recruit specialized archival staff to resolve document overlap and accelerate retrieval processes for optimized organizational productivity.